High tunnel propagation systems for organic sweetpotato - Hoppenstedt, Zachary (Kansas State University, 2018)
Sweetpotatoes [Ipomoea batatas (L.) Lam.] are nutritious, easily stored and marketed, well-adapted to organic production, and fit large or small farming operations. Commercial production of propagules for sweetpotato, vine cuttings known as slips, is concentrated among a few coastal states. Consequently, growers in the Central United States have limited access to planting material. Considering the crop’s sensitivity to cold climates and the increasing use of high tunnels (HTs) in the region, the implementation of HT production systems could be a viable mechanism for increasing the distribution of sweetpotato nurseries across the US. The goal of this project was to investigate the production of slip propagation beds in HT systems at two research stations in Northeast and South Central Kansas. Trials were conducted in 2016 and 2017 to compare yield and quality of organic slips grown in HTs and the open-field (OF). Additionally, a split-plot design was utilized inside the HT to compare slip yields for three planting densities (45, 65 and 85-seed roots/m²). Slips grown in the two systems (HT and OF) were field-planted to elucidate the impact of the system on subsequent root tuber yields and grade. HT enterprise budgets were developed to determine what the potential economic impact is for growers that wish to implement this system and to identify the appropriate planting density based on cost and return. In 2016, the HT plots produced more slips than in the OF (P < 0.05), and the overall average slip number was 226.7 in the HT and 147.8 in the OF across both years. However, slips grown in the HT had significantly fewer nodes, less foliage, and compactness (P < .001). The field performance study showed slightly greater average marketable storage root yield from slips produced in the OF (P = NS), but the quantity and distribution of graded storage roots were similar between slips grown in the HT and OF treatments. Increased planting density treatment corresponded with greater average slip yield across all harvests, but was only statistically significant during 1st harvest of 2016. The positive correlation between slip yield and planting densities plateaued between 65 and 85-seed roots/m². When using foundation seed roots the optimum profit for enterprise budgets was achieved at the 65-seed root planting density. The use of 25% foundation and 75% on-farm produced seed roots at 85-seed root density generated $1.05/ft² profit in HT—using the more manual cultural practices and equipment of two case studies. The results of these trials suggest that slip production in HTs may provide growers in the Central and Northern regions of the U.S. a viable technology for developing their own sweetpotato propagation schedule, without compromising plant yield or storage root production. When compared to other common HT crop budgets, our data suggest that HT slip production is an economically-viable system for growers who wish to incorporate slip propagation beds into their HT rotations.
Keywords: Sweetpotato; Ipomoea batatas; High tunnel; Organic; Slip; Economic